Is the Value Premium Dead? Forecasting Value–Growth Cycles with the Implied Value Premium - Li, Yan; Ng, David Tat-Chee; Swaminathan, Bhaskaran (Journal of Financial and Quantitative Analysis, 2026)
We introduce the implied value premium ( IVP ), the difference between the implied costs of capital of value and growth stocks, to predict time variation in the ex post value premium. During 1977–2023, IVP is the strongest predictor of the ex post value premium. It also predicts the investment premium, consistent with the Investment CAPM. However, IVP ’s ability to predict the difference in cumulative abnormal returns around quarterly earnings announcements of value and growth stocks suggests that mispricing may also play a role. Overall, our results suggest that recent value underperformance reflects cyclical variation rather than a permanent shift.